Q: What is -5c plus d equals 2c?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(a-d)/2c=b

4ac + 2ad + 2bc +bd = 2a*(2c + d) + b*(2c + d) = (2c + d)*(2a + b)

c - 5d = 2 2c + d = 4 Multiply eqn 1 by 2: 2c - 10d = 4 Subtract this from eqn 2: 0c + 11d = 0 which implies that d = 0 Then, by eqn 1, c = 2

(2a + b)(2c + d)

(2a + b)(2c + d).

Related questions

(a-d)/2c=b

4ac + 2ad + 2bc +bd = 2a*(2c + d) + b*(2c + d) = (2c + d)*(2a + b)

c - 5d = 2 2c + d = 4 Multiply eqn 1 by 2: 2c - 10d = 4 Subtract this from eqn 2: 0c + 11d = 0 which implies that d = 0 Then, by eqn 1, c = 2

If a=2bc+db= (a - d) / 2c If a=2b+c b=1/2(a-c)

The expression is 5d+2c and the unknown variables are d and c

(2a + b)(2c + d)

(2a + b)(2c + d)

(2a + b)(2c + d).

the answer is a

(3a - 2c)(b - d)

I--2a+b=2c+2d II--2a+b=c+2d III--a+2b=3d * Here if we perform (I)-(II), we get, c=0 * Using the c we can prove b=0 using (I)-(III). * Now replace 'b' & 'c' as 0 in (I), then we get a=d. Email me at yash2008gates@gmail.com for any queries. I will be very thankful to receive your queries.

(7 x 7) - (5 x 3)